Effects of Combined Simultaneous and Sequential Endostar and Cisplatin Treatment in a Mice Model of Gastric Cancer Peritoneal Metastases - Lin Jia; Shuguang Ren; Tao Li; Jianing Wu; Xinliang Zhou; Yan Zhang; Jianhua Wu; Wei Liu (Gastroenterology Research and Practice)
Objective. Aimed to study the effects of endostar and cisplatin using an in vivo imaging system (IVIS) in a model of peritoneal metastasis of gastric cancer. Methods. NUGC-4 gastric cancer cells transfected with luciferase gene (NUGC-4-Luc) were injected i.p. into nude mice. One week later, mice were randomly injected i.p.: group 1, cisplatin (d1–3) + endostar (d4–7); group 2, endostar (d1–4) + cisplatin (d5–7); group 3, endostar + cisplatin d1, 4, and 7; group 4, saline for two weeks. One week after the final administration, mice were sacrificed. Bioluminescent data, microvessel density (MVD), and lymphatic vessel density (LVD) were analyzed. Results. Among the four groups, there were no significant differences in the weights and in the number of cancer cell photons on days 1 and 8 (P>0.05). On day 15, the numbers in groups 3 and 1 were less than that in group 2 (P<0.05). On day 21, group 3 was significantly less than group 2 (P<0.05). MVD of group 4 was less than that of groups 1 and 2 (P<0.01). There was no significant difference between groups 2 and 3 (P>0.05) or in LVD number among the four groups (P>0.05). Conclusions. IVIS® was more useful than weight, volume of ascites, and number of peritoneal nodules. The simultaneous group was superior to sequential groups in killing cancer cells and inhibiting vascular endothelium. Cisplatin-endostar was superior to endostar-cisplatin in killing cancer cells, while the latter in inhibiting peritoneal vascular endothelium.